1985
DOI: 10.23986/afsci.72188
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplementation of grass silage with rapeseed meal or Gasol-treated barley on the performance of growing cattle

Abstract: Grass silage was offered ad libitum to 16 Ayrshire cattle in a 2 x 2 factorial experiment lasting 196 days. The silage was supplemented with barley preserved with 0.85 % of propionic acid (PAB) or 1.28 % Gasol solution (GB) 45 g DM/kg W0.75. Four of the animals in PAB and GB groups received no protein supplement(NPS) and four of the animals in both groups received extracted rapeseed meal as protein supplement(RSM). RSM was fed according to UDP (undegradable feed protein) requirements. The average age of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…In agreement with Huuskonen et al (2007a), RSM supplementation had no effect on OMD in the present trial, which is in line with the lack of significant effect on DMI. Inversely, the CP digestibility was slightly higher with the RSM diet than with the C diet, which is in accordance with the results of Huhtanen et al (1985), Aronen and Vanhatalo (1992), Aronen et al (1992) and Huuskonen et al (2007a). Some of the increased apparent digestibility of CP on the protein-supplemented diets may have reflected the better digestibility of protein, while most of the increase is only apparent, being attributable to the decreased proportion of faecal metabolic nitrogen recovered in faeces with increasing CP content (Minson 1982).…”
Section: Discussion Feed Intake and Diet Digestibilitysupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with Huuskonen et al (2007a), RSM supplementation had no effect on OMD in the present trial, which is in line with the lack of significant effect on DMI. Inversely, the CP digestibility was slightly higher with the RSM diet than with the C diet, which is in accordance with the results of Huhtanen et al (1985), Aronen and Vanhatalo (1992), Aronen et al (1992) and Huuskonen et al (2007a). Some of the increased apparent digestibility of CP on the protein-supplemented diets may have reflected the better digestibility of protein, while most of the increase is only apparent, being attributable to the decreased proportion of faecal metabolic nitrogen recovered in faeces with increasing CP content (Minson 1982).…”
Section: Discussion Feed Intake and Diet Digestibilitysupporting
confidence: 90%
“…In some earlier studies on growing dairy bulls with separate feeding the RSM supplementation increased the intake of hay (Aronen 1990) or grass silage (Aronen 1990, Aronen and Vanhatalo 1992a but, for example, Huhtanen et al (1985Huhtanen et al ( , 1989 Differences between the diets were compared using an a priori test (Dunnett's test) so that comparison of the diets was based on the C diet. Contrasts: (1 = C vs. RSM), (2 = C vs. WDS),…”
Section: Discussion Feed Intake and Diet Digestibilitymentioning
confidence: 99%
“…However, in experiments with grass silage, results have been somewhat contradictory. Huhtanen et al (1985), Steen (1988), Aronen (1990) and Moloney (1991) did not find any change in voluntary grass silage intake when protein supplements were included in the diet, while Aronen (1991) and Aronen and Vanhatalo (1992) recorded an increased grass silage intake with a resultant enhancement in LWG of bulls.…”
Section: Introductionmentioning
confidence: 98%
“…Special attention was paid to possible interactions between the stage of maturity of grass for silage and the type of the supplementary concentrates (i.e., barley or barley together with RSM) to find out whether the effect of RSM depends on the protein and energy content of the grass silage. Similarly, the interaction between the protein supplementation and the level of concentrate in the diet was ofinterest, because earlier findings by Waterhouse et al (1983) suggested that lower responses to protein supplementation were to be expected for diets with a high concentrate level.In some experiments (Hakkola 1985, JokiTokola 1991, Aronen and Vanhatalo 1992), the positive effect of protein supplementation on LWG was sustained throughout the experiment, while in others (Huhtanen et al 1989, Aronen 1990) the positive effect of RSM on LWG was restricted to the early phase of the growth period (i.e., live weight below 300 kg). Therefore, the manner in which the treatment effects and their possible interactions change with the phase of the production experiment was examined in the present study.…”
mentioning
confidence: 99%
See 1 more Smart Citation